FRI0179 Comparative Effectiveness of Biologic Disease Modifying Anti-Rheumatic Drug Therapy in US Veterans with Rheumatoid Arthritis. (10th June 2014) - Cannon, G.W.; He, T.; Teng, C.-C.; Leng, J.; Lu, C.-C.; Tang, D.; Shah, N.; Harrison, D.J.; Sauer, B.
Abstract : Background: Comparison of effectiveness of biologic disease modifying anti-rheumatic drugs (DMARDs) in clinical practice may provide important insight into their clinical benefit in patients with rheumatoid arthritis (RA). A recent validated algorithm is available to evaluate clinical effectiveness in US veterans. 1 Objectives: To compare the effectiveness of abatacept (ABA), adalimumab (ADA), etanercept (ETN), infliximab (INF), and rituximab (RIT) in US veterans with RA and assess the reasons for failure. Methods: National Veterans Affairs (VA) pharmacy and administrative databases were evaluated on all US veterans initiating biologics from Jan 1, 2008 to Jan 1, 2012 and followed until Jan 1, 2013 to allow ≥1-year of follow-up per patient. The analysis was limited to the first treatment course beginning ≥180 days after VA enrollment, consistent with a new biologic initiation and agents with ≥100 dispensing episodes. The validated effectiveness algorithm is based on administrative claims data. Medications were classified as effective if all of the following criteria were met: high adherence, Medication Possession Ratio (MPR) >80% for self-injected biologic or receiving at least 80% of the minimum recommended number of infusions, no biologic dose increase, no switching biologics, no new non-biologic disease modifying antirheumatic drugs (DMARD), <2 intra-articular injections, no new glucocorticoids or glucocorticoid dose increases. 1 Results: During the study period, 19, 244 RA patients were treated with biologics; 9, 979 had 1-year of follow-up and 4, 704 patients had their first course beginning >180 days after VA enrollment. Conclusions: Algorithm-defined effectiveness was higher for injectable tumor necrosis factor inhibitors (ADA, ETN) than for infused biologics, ABA, INF, and RIT. Major factors associated with lower effectiveness were low adherence and biologic dose escalation. References: Curtis et al. Arthritis Res Ther, 2011, 13(5), R155. Acknowledgements: Research funded by VA Research Program and Immunex Corporation, a wholly owned subsidiary of Amgen Inc., and by Wyeth, which was acquired by Pfizer Inc. in October 2009. Disclosure of Interest: G. Cannon: None declared, T. He: None declared, C.-C. Teng: None declared, J. Leng: None declared, C.-C. Lu: None declared, D. Tang Shareholder of: Amgen, Employee of: Amgen, N. Shah Shareholder of: Amgen, Employee of: Amgen, D. Harrison Shareholder of: Amgen, Employee of: Amgen, B. Sauer: None declared DOI: 10.1136/annrheumdis-2014-eular.1903